Do emergency medicine journals promote trial registration and adherence to reporting guidelines? A survey of "Instructions for Authors". Issue 1 (December 2016) - Sims, Matthew; Henning, Nolan; Wayant, C.; Vassar, Matt
Abstract Background The aim of this study was to evaluate the current state of two publication practices, reporting guidelines requirements and clinical trial registration requirements, by analyzing the "Instructions for Authors" of emergency medicine journals. Methods We performed a web-based data abstraction from the "Instructions for Authors" of the 27 Emergency Medicine journals catalogued in the Expanded Science Citation Index of the 2014 Journal Citation Reports and Google Scholar Metrics h5-index to identify whether each journal required, recommended, or made no mention of the following reporting guidelines: EQUATOR Network, ICMJE, ARRIVE, CARE, CONSORT, STARD, TRIPOD, CHEERS, MOOSE, STROBE, COREQ, SRQR, SQUIRE, PRISMA-P, SPIRIT, PRISMA, and QUOROM. We also extracted whether journals required or recommended trial registration. Authors were blinded to one another's ratings until completion of the data validation. Cross-tabulations and descriptive statistics were calculated using IBM SPSS 22. Results Of the 27 emergency medicine journals, 11 (11/27, 40.7%) did not mention a single guideline within their "Instructions for Authors, " while the remaining 16 (16/27, 59.3%) mentioned one or more guidelines. The QUOROM statement and SRQR were not mentioned by any journals whereas the ICMJE guidelines (18/27, 66.7%) and CONSORT statement (15/27, 55.6%) were mentioned most often. Of the 27 emergency medicine journals, 15 (15/27, 55.6%) did not mention trial or review registration, while the remaining 12 (12/27, 44.4%) at least mentioned one of the two. Trial registration through ClinicalTrials.gov was mentioned by seven (7/27, 25.9%) journals while the WHO registry was mentioned by four (4/27, 14.8%). Twelve (12/27, 44.4%) journals mentioned trial registration through any registry platform. Discussion The aim of this study was to evaluate the current state of two publication practices, reporting guidelines requirements and clinical trial registration requirements, by analyzing the "Instructions for Authors" of emergency medicine journals. In this study, there was not a single reporting guideline mentioned in more than half of the journals. This undermines efforts of other journals to improve the completeness and transparency of research reporting. Conclusions Reporting guidelines are infrequently required or recommended by emergency medicine journals. Furthermore, few require clinical trial registration. These two mechanisms may limit bias and should be considered for adoption by journal editors in emergency medicine. Trial registration UMIN000022486